’Pax’ and imperialism: from Republic to Principate throughout civil wars - Cunha, Macsuelber de Cássio Barros (Romanitas - Revista de Estudos Grecolatinos, 2019)
Review of: CORNWELL, Hannah. Pax and the Politics of Peace: Republic to Principate. Oxford: Oxford University Press, 2017. 272 p.